Comparative Study of Clinical Profile in Patients With Solitary vs Multiple Gallstones - Dev, Kapil; Sarfraz, Khurram; Shah, Syed Amir; Yuvraj, Sanjay Neelam; Sindhu, Shaista; Mehak, . (Biological and Clinical Sciences Research Journal, 2025)
Gallstones are a common biliary pathology, posing a significant global health burden. The worldwide prevalence of gallstones is approximately 10-15% among adults, with higher rates reported in developed countries due to dietary habits and lifestyle factors1. In developing nations, including Pakistan, the prevalence of gallstone disease ranges between 15% and 20% with a higher occurrence in females compared to males. Objective: To compare the clinical profiles of patients with solitary gallstones versus those with multiple gallstones in a Pakistani population. Study design: Prospective observational study. Place and duration: Department of General Surgery, Combined Military Hospital, Hyderabad, for 6 months, i.e., from Oct/2024 till March/2025. Methods: A total of 141 patients who fulfilled the selection criteria were included. Patients were divided into two groups based on the number of stones in the gallbladder as revealed on ultrasonography, i.e., Group A (solitary gallstones; n=71) and Group B (multiple gallstones; n=70). All patients underwent laparoscopic cholecystectomy, and outcomes were assessed and subjected to statistical analysis. Results: The median (IQR) age of patients in Group A was 45 (13) years, and in Group B was 42 (13) years (p=0.601). The median (IQR) intraoperative duration in Group A was 42 (4) minutes and in Group B was 41 (7) minutes (p=0.016). The median (IQR) duration of stay at the hospital was 6 (2) days in Group A and 4 (1) days in Group B (p=0.000). Pain was the commonest symptom in both groups, and there was no significant difference in terms of clinical presentation between the two. Conclusion: In patients with gallstones, there was no significant difference in the clinical presentations of multiple versus solitary gallstones; however, there was a significant difference in terms of intraoperative duration, intraoperative findings, and duration of hospitalization.